Determination of friction performance influence in the system "body–bogie" on the freight car dynamics - Myamlin, S. V.; Neduzha, L. O.; Shvets, A. O. (Science and Transport Progress, 2014)
Purpose. The main requirements for the design of a new generation of cars, according to the Program of rolling stock renovation, are the requirements reducing the operating costs and increasing the cost-effectiveness of their use, taking into account the achievements of scientific and technical thought. Due to the urgency of this subject the paper is devoted to the study of the friction coefficient influence in the bearing connection «center plate – center bowl – bearers»of freight cars on their main dynamic parameters – coefficients of horizontal and vertical dynamics, body acceleration, frame strength, derailment stability factor. Methodology. The study was conducted by numerical integration and mathematical modeling of the freight car dynamic loading using the software package «Dynamics of Rail Vehicles» («DYNRAIL»). Findings. Investigations have shown that the safety movement parameters are influenced by both the friction parameters in bearing connection «center plate – center bowl – bearers» of freight cars in empty and loaded state with bogies TSNII-X3 (model 18-100). Effect have other components of freight car dynamics, namely: radii of curved track sections, height of outer rail, etc. Originality. The author investigated the friction influence on the car dynamic loading using new approaches to solving the problem of predicting the rolling stock dynamics. Prediction was carried out on the basis of significantly updated theoretical material that covers all history of the friction theory and includes the results of recent experimental studies because of the speed on the straights and curves of small-and medium-range sections of the road.Practical value. The obtained results have practical orientation. During the research and after modeling with the improved method of accounting of friction processes dependencies of main dynamic parameters of a four-freight gondola on the value of the friction coefficient in the "body – bogie" with regard to speed were obtained. The results of scientific studies have found their scientific use in a number of author publications in the special scientific and popular publications.